Increases in nitrogen use efficiency decrease nitrous oxide emissions but can penalize yield in sugarcane - Chalco Vera, Jorge Elías (2021)
Nitrogen (N) fertilization strategies focused on increasing nitrogen use efficiency (NUE) and decreasing nitrous oxide (N2O) emissions are important for sustainable crop production. In sugarcane, however, a joint assessment of NUE, N2O emissions and yield is still required. We aimed to establish, in a subtropical sugarcane cropping system, if variations in NUE (by decreasing rates or changing formulations of N fertilization) allow decreasing N2O emissions and, to what extent, yield is penalized. Four fertilization treatments were used: without fertilizer, with low and high urea fertilization (55 and 110 kg N ha−1) and with ammonium nitrate fertilization (110 kg N ha−1). There was a significant negative relationship between N2O emissions and NUE. At high N rates (110 kgN ha−1) ammonium nitrate produced 37% higher cumulative N2O emissions and 13 and 12% lower NUE and cane yield, respectively, than urea. The highest N2O emissions of the ammonium nitrate treatment occurred within 48 hs after N fertilization and were mainly associated with the direct addition of nitrate (NO3−–N). Results showed that, for the environmental conditions of Tucuman (Argentina), NUE above 160 kg of cane per kg of N available in soil penalized cane yield, whereas NUE below 140 kg of cane per kg of N available in soil penalized N2O emission abatement.